Herpesviruses in the Activated Phosphatidylinositol-3-Kinase-δ Syndrome - Cohen, Jeffrey I. (Frontiers in Immunology, 2018)
The phosphatidylinositol-3-kinase (PI3K)/Akt pathway is important for multiple stages of herpesvirus replication including virus entry, replication, latency, and reactivation. Recently, patients with gain-of-function mutations in the p110δ catalytic subunit of PI3K or in the p85 regulatory subunit of PI3K have been reported. These patients have constitutively active PI3K with hyperactivation of Akt. They present with lymphoproliferation and often have infections, particularly recurrent respiratory infections and/or severe virus infections. The most frequent virus infections are due to Epstein-Barr virus (EBV) and cytomegalovirus (CMV); patients often present with persistent EBV and/or CMV viremia, EBV lymphoproliferative disease, or CMV lymphadenitis. No patients have been reported with CMV pneumonia, colitis, or retinitis. Other herpesvirus infections have included herpes simplex pneumonia, recurrent zoster, and varicella after vaccination with the varicella vaccine. Additional viral infections have included adenovirus viremia, severe warts, and extensive molluscum contagiosum virus infection. The increased susceptibility to virus infections in these patients is likely due to reduced numbers of long-lived memory CD8 T cells and increased numbers of terminally differentiated effector CD8 T cells.